The Relationship Between Economic Growth, Energy Consumption And Trade With Environmental Degradation: The Case Study Of Five Asean Countries - Saboori, Behnaz (2013)
Recent studies in examining the Environmental Kuznets Curve (EKC) emphasized the lack or even negligence of the energy consumption and trade openness role in shaping the EKC. Previous empirical studies, to certain degree have not considered the effect of dirty industry import and dirty industry export in examining the EKC model. This study examined the relationship between economic growth and CO2 emissions based on the EKC hypothesis in the five selected ASEAN countries namely Indonesia, Malaysia, the Philippines, Singapore and Thailand or also known as the ASEAN-5. The study also investigated the effect of total energy consumption and trade openness on these ASEAN countries’ emissions and in shaping the EKC. The study further included the effect of dirty industry import to the ASEAN-5 countries and dirty industry export from these countries to their main trading partners to the framework to examine the effect of Pollution Haven Hypothesis (PHH) on the existence of the EKC. Employing the Autoregressive Distributed Lag (ARDL) approach, the reduced-form EKC model was not able to demonstrate the accurate relationship between CO2 emissions and economic growth. Energy consumption and trade openness played a significant role in shaping the EKC in Malaysia, Singapore and Thailand. In Singapore, the EKC existed based on the reduced-form model. In Thailand there was evidence of the EKC when energy consumption was included to the model. However, when the model was further extended by trade openness, evidence of the EKC also existed in Malaysia.